Comprehensive review of headache medicine - Levin, Morris, 1955- (Oxford University Press, 2008)
Headache Medicine has recently become an official medical subspecialty. Practitioners who specialize in the field come from many different backgrounds including neurology, internal medicine, anesthesiology, rehabilitation medicine, family medicine, psychiatry, dentistry and others. A great deal of research is being done in HM, and, as a result, the field is one which is growing rapidly in every way. Interestingly, most patients with headache are not being treated by specialists in HM, in large part because of the vast numbers of patients requiring medical attention for headache disorders, and.